Reinforced Soft Soil by CSV with/without Polypropylene fibres: Experimental and Numerical analysis. (Fracture and Structural Integrity, 2021)
Columns of mixed soil-sand-cement (CSV), is one of the most unknown used methods for soft soil stabilization that has not been studied before. To this end, in this paper, consolidated drained (CD) triaxial compression tests after have been cured for 28 days, were carried out to investigate the effectiveness of CSV, which is mainly used to reinforce soft soil. Then, the influence of soft soil content (25%, 50%, 75%) on materials of CSV with/without polypropylene (PP) fibers is established. The percentages of soft soils (50%, 75%) are experimentally doable and the remaining percentage (25%) was not successfully experimented; for this exact reason, an empirical formula is established based on the design of experiments (DOE) for calculating the soft soil’s characteristics. Then a numerical study using PLAXIS 3D is developed for studying the embankment building on soil which is reinforced by CSV. It is found that the efficacy of the reinforcement of the soft soil by CSV with/without PP fibers provides with satisfying results. Moreover, the less amount of soft soil on CSV materials the better for deviatoric stress, axial strain, the effective cohesion, the effective friction angle and modulus of elasticity E50. Additionally, when PP fibers is added to CSV material, experimental results were strongly affected. As far as the numerical study, the embankment building on the soil  that is reinforced by the CSV shows an improvement in the level of displacement in the three directions, the total displacement and security factor. The variation of materials of CSV content with/without PP fibers, a diverse combination with a relatively lower effect can be easily remarked on the achieved results.
Keywords: Soft soil; Triaxial; PLAXIS 3d; Method design of experimental (DOE); Columns sand-cement (CSV); Polypropylene fibers